The expression of arginase-1, keratin (K) 8 and K18 in combined hepatocellular-cholangiocarcinoma, subtypes with stem-cell features, intermediate-cell type. Issue 10 (11th March 2016) - Akiba, Jun; Nakashima, Osamu; Hattori, Satoshi; Naito, Yoshiki; Kusano, Hironori; Kondo, Reiichiro; Nakayama, Masamichi; Tanikawa, Ken; Todoroki, Keita; Umeno, Yumi; Nakamura, Ken; Sanada, Sakiko; et al.
Abstract : Aims: The WHO classification describes that combined hepatocellular-cholangiocarcinoma, subtypes with stem-cell features, intermediate-cell subtype (CHC-INT) is composed of tumour cells with features intermediate between hepatocytes and cholangiocytes. However, we previously reported that CHC-INT showed a high positive rate of biliary markers, but the expression of hepatocyte paraffin (HepPar)-1 was low. In this study, we examined the expression of other hepatocyte markers, such as arginase-1 (Arg-1), keratin (K) 8 and K18 in CHC-INT in order to examine the utility of pathological diagnosis in CHC-INT. Methods: We performed immunohistochemistry (IHC) of Arg-1, K8 and K18 using 32 previously diagnosed as CHC-INT. Immunoreactivity was evaluated with grading from 0 to 4 according to the distribution area of positive cells. The obtained findings of Arg-1, K8 and K18 were compared with those of K7, K19 and HepPar-1. Results: Out of the 32 cases, 22 (68.8%) cases were positive for Arg-1. Twenty-five (78.1%) were positive for K8. The IHC scores of Arg-1 and K8 were significantly higher than those of HepPar-1, but significantly lower than those of K7 and K19. The K18 expression was widely observed in all cases (100%). The IHC score of Arg-1 and K8 in CHC-INT was intermediate between hepatocellular carcinoma and cholangiocarcinoma. Conclusions: Arg-1 and K8 were good markers to identify intermediate cells between hepatocytes and cholangiocytes. These can be useful markers for pathological diagnosis of CHC-INT, which usually has wide histological diversities, in combination with other hepatocytic and/or cholangiocytic markers.